EFEK PENGGUNAAN SUSU SKIM DENGAN PENGENCER TRIS KUNING TELUR TERHADAP DAYA TAHAN HIDUP SPERMATOZOA SAPI - Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2016)
This research was carried out in the laboratory of regional technical services Unit (UNIT) Petyernakan Agency of Jambi province, began on 24 April 2016 until May 22, 2016This research aims to know the effect of the use of skim milk with diluent tris egg yolk endurance against live spermatozoa. The research method used alphabets experiment, using Random Design Group (RAK) and 5 (five) treatment and 5 (five) groups. Asthe group is ejakulat. As for the moderate i.e. P0 = 100% + skim milk without diluent tris yolk, P1 = 95% skim milk + tris egg yolks 5%, P2 = 90% skim milk + tris egg yolks 10%, P3 = 85% skim milk + tris egg yolk 15%, P4 = skim milk 80% + 20% yolk tris.The results showed that the granting of skim milk with egg yolk tris diluent on P3 treatment gives a very real influence (P < 0.01) in maintaining the rate of decrease inendurance live bovine spermatozoa.Results of the study it was concluded that the awarding of the diluent skim milk until level 15% gives the best result, so was able to suppress the rate of decrease in endurance live bovine spermatozoa are stored for 2 days at a temperature of 5 ℃.Keywords: skim milk, egg yolks, endurance live spermatozoa bovine